Piezo in the eye: expression, distribution and roles in ocular diseases - Zhu, Li; Ren, Shouyan; He, Shuang; Liu, Meifang; Hou, Fei (Frontiers in Physiology, 2025)
Piezo channels are currently known to be the most sensitive molecular mechanoreceptors. Piezo can respond to membrane tension, sag, shear force, tensile and other mechanical stimuli, produces fast inactivation, small conductance, and low threshold current. In eukaryotic cells, Piezo has two family members: Piezo1 and Piezo2. Functionally, Piezo1 detects whole-membrane tension changes, including swelling and compression. Piezo2 is more likely to sense specific mechanical stimuli, including touch and airway stretching. In the ocular system, Piezo1 and Piezo2 are expressed across various cells and tissues. This article provides a comprehensive review of the expression, distribution, and function of Piezo channels in ocular tissues, offering novel insights for the treatment of eye diseases.